Caracterização mecânica de um compósito de matriz poliéster insaturado reforçado com fibras de sisal em diferentes orientações utilizando correlação digital de imagens - Silva, Fernanda Monique da (2018)
The use of composite materials of polymer matrix reinforced with natural fibers, such as sisal, is of great relevance for the environmental and social benefit, since there is a large contingent of labor involved in the implantation, maintenance, harvest and fiber defibration. For this reason, this work has the objective of confection and mechanical characterization of composites of unsaturated polyester matrix reinforced with sisal fibers. This preparation was done by the method of molding by manual lamination, because it is suitable the conditions available in the regions producing sisal. Traction tests were performed on sisal fibers and unidirectional composites with and without alkaline treatment at different concentrations (2% and 5%) as a way of evaluating the influence of this on their mechanical properties. In the resin and in the composites with the fibers, without treatment, in the longitudinal and transverse directions and in those with different orientations, [90, 0, 90] and [0, 90, 90,0], tensile and tensile tests were carried out. to evaluate the influence of fiber orientation on its properties. Finally, composites with orientation [0, 90, 90, 0] were made with different fiber volume concentrations (10%, 20% and 30%) to evaluate the influence of the concentration on its mechanical tensile properties. The Digital Image Correlation (CDI) technique was used in the tensile tests as an alternative to measure the displacement and deformation fields along the surface of these materials. The loss of mass, density and mechanical properties of sisal and unidirectional composites were increased as the NaOH concentration of the chemical treatment was increased. The unidirectional composites [0] had good mechanical properties, whereas those tested in the transverse direction of the fiber [90] were low. The composites oriented in the two configurations presented similar results. The tensile strength of the composites increased with increasing fiber concentration